Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

how could i solve the PDE (without boundary or other initial conditions)

$ 1= y\partial _{y}f(x,y) -x \partial _{x}f(x,y) $

share|cite|improve this question
What do you mean by "solve"? Find all functions that solve it? Without conditions, the solution is not unique. – joriki Apr 10 '12 at 10:32
up vote 1 down vote accepted

One solution would be:

$f(x,y) = xy - log(x)$

But so would:

$f(x,y) = n\cdot xy - log(x)$

In general, you need a boundary condition to solve a first order PDE.

share|cite|improve this answer
ok , thanks is it possible to get ALL the solutions of $ f(x,y) $ into a closed expression :) – Jose Garcia Apr 10 '12 at 10:33
The equation is linear, so taking the difference between two solutions $f_1$ and $f_2$ you have that $y\partial_y(f_1 - f_2) - x\partial_x(f_1-f_2) = 0$, so every solution is a specific solution plus some homogeneous solution. The specific solution is given above by nbubis as $f_0 = \log(|x|)$. Any homogeneous solution has to be constant on the integral curves of $x\partial_x - y\partial_y$, and hence can be written as $g = g(xy,\mathop{sgn}(x))$. That is, as a function depending only on the product $xy$ and on the sign of the variable $x$. The second dependence is because outside $xy=0$... – Willie Wong Apr 10 '12 at 11:29
... the level curves $\{xy = c\}$ (which are the integral curves of $x\partial_x - y\partial_y$) have two connected components, and the function is allowed to be different on the components. The two components can be distinguished by the sign of the $x$ variable there. – Willie Wong Apr 10 '12 at 11:30



Follow the method in

$\dfrac{dx}{dt}=x$ , letting $x(0)=1$ , we have $x=e^t$

$\dfrac{dy}{dt}=-y$ , letting $y(0)=y_0$ , we have $y=y_0e^{-t}=\dfrac{y_0}{x}$

$\dfrac{df}{dt}=-1$ , letting $z(0)=F(y_0)$ , we have $f(x,y)=F(y_0)-t=F(xy)-\ln x$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.